Un caso de isoinmunización materna por el antígeno c (hr') - Loría, Rodrigo (1955)
1. The first case in Costa Rica of maternal isoimmunization due to the c(hr') factor is described with the offspring being affected by hemolytic disease of the newborn. 2. The case is considered highly interesting because it is autochthonous, with the immuno-genetic factors favoring the devolpment of the process. 3. An exchange transfusion using the umbilical vein was performed with 500 ce. of blood. 4. A rapid cure of the jaundice and the anemia was obtained, and the patient was discharged in a very good condition.